A Tentative Approach to Mapping Street Space: A Case Study of Chinese Central Urban Districts - Lian Tang; Wowo Ding (Footprint)
This paper focuses on exploring a quantitative approach to mapping street space. Characteristics of street space can hardly be described and explained using only the traditional architectural forms of street space. The difficulty arises because of the lack of relevance between these forms and people’s activities in them.